Development models of the dialogue with privacy invasion elements - Zhupinskaya, Anna V. (Journal of the Belarusian State University. Philology, 2023)
The article considers the development of the dialogue that contains privacy invasion (violation of personal borders) conducted by the journalist and appropriate response realised by the interviewee. The research is made on the basis of Russian and English media interviews. The aim of the study is to identify typical development models of the dialogue with privacy violation elements. The models can be identifed according to interviewee’s reaction to privacy invasion and interviewer’s degree of persistence. The article states that the dialogue with privacy invasion elements develops according to four basic models, three of which can be further complicated by inclusion of question-answer cycles in their structure. Besides the mixed dialogue model is identifed. The mixed model combines elements of basic models. Comparative analysis proved that dialogue models are identical in Russian and English media interviews. Also a general algorithm of the dialogue with privacy invasion elements was created.
Keywords: media interview; privacy; invasion strategy; defense strategy; dialogue model; basic model; complicated variant of model; mixed model